Disoriented Disciplines: China, Latin America, and the Shape of World Literature. By Rosario Hubert. Evanston: Northwestern University Press, 2024. 324 pages - Ran, Wei (Latin American literary review, 2025)
Rosario Hubert’s Disoriented Disciplines is not merely a historiographical survey of literary exchanges between China and Latin America; rather, it accomplishes something far more ambitious: uncovering the infrastructural foundations upon which twentieth-century Latin American writers and artists—ranging from turn-of-the-century modernismo to contemporary figures still active in cultural and political spheres, such as Santiago Gamboa, Juan Gabriel Vásquez and Colombia’s current ambassador to China and filmmaker Sergio Cabrera, one of Latin American “red diapers”—have constructed their descriptions and narratives about China.